Pemanfaatan Whatsapp dalam Proses dan Asesmen Pembelajaran Jarak Jauh Selama Pandemi Covid-19 - Fahmi Yahya; Musahrain Musahrain; Hermansyah Hermansyah; Indah Dwi Lestari (Indonesian Publication Center, 2022)
The Covid-19 pandemic forced a drastic shift in the implementation of learning in Indonesia, from face-to-face instruction to online distance learning. Amid limited internet access, data quota, and devices, WhatsApp emerged as one of the most widely used instant messaging applications among teachers and students due to its accessibility, simplicity, and relatively light data usage. This study aims to narratively describe how WhatsApp was utilized in the learning process and in the implementation of assessment during the Covid-19 pandemic, and to identify the advantages, obstacles, and strategies used by educators to optimize the application. This research employs a qualitative approach with a narrative literature review method of studies published between 2019 and 2021. The results show that WhatsApp was used in the learning process through text messages, voice and video calls, and the sharing of documents, images, and audio recordings to deliver materials, give instructions, and build teacher-student interaction. In terms of assessment, WhatsApp was used to distribute questions, collect assignments in the form of photos or documents, provide feedback, and conduct affective assessment through observation of student activity in class groups. However, several obstacles were found, such as limited internet quota, signal disruption, lack of face-to-face interaction, and the potential for academic dishonesty in completing assignments. The study concludes that WhatsApp is an accessible and effective alternative medium for distance learning, but requires appropriate pedagogical strategies and assessment management to maintain the quality of learning.